Baby Huey (and other cartoons) - Meyer, Carl; Cinetel Films ([Los Angeles, CA] : Famous Studios Production, 1945)
His Mama is the only one who love Baby Huey, an overgrown clumsy ugly duckling. The other Mamas and their broods shun him like the plague and make his little life miserable. But when a ferocious fox attacks the barnyard, Huey comes to the rescue of one and all. Huey is a hero basking in his new-found popularity.
Baby Huey, the over-sized duck, is enrolled in kindergarten but his size and clumsy attempts to fit in causes such havoc that he is expelled by the teacher. His mother then hires a private tutor, who is led a life of misery due to Huey's efforts to do good that unintentionally backfire. But the tutor winds up in the ocean---unless Huey lived on a shark-invested lake---and and is about to become a shark meal but Huey saves his life...and gets his diploma as a reward from the grateful tutor.
A very stupid and superstitious cat awakens and goes through his usual gyrations of ensuring he will not have an unlucky day, making sure he get out of the right side of the bed and other rituals, and then starts his search for breakfast. He captures Buzzy the Crow, places him between two slices of bread and prepares to eat him. But Buzzy, smarter than the average crow since he is a cartoon parody of Eddie Anderson's "Rochester" character, has no intentions of being a cat's sandwich breakfast, knows the cat is superstitious and causes the cat to spill the salt, knowing the cat will have to release him in order to throw some salt over his shoulder. This goes on for a while as Buzzy calls the cat's attention to something that has to be counter-acted by the cat. And, just as the cat seems to have Buzzy about to become a lunch---they carried on all the way through brunch---the cat flees in terror as he sees a fellow cat---black in color---about to cross his path.
A group of mice living within the walls of a house forms an orchestra. However, the music disturbs the cat who also lives there, so the cat sets out to eliminate the mice.
Herman the mouse attempts to break up the smarmy friendship between the cat and dog of the house in order to raid the icebox.
Quack-a doodle-doo / Paramount presents a Noveltoon ; direction, I. Sparber ; animation, Dave Tendlar, Tom Golden ; story, Carl Meyer, Jack Mercer, Martin Taras. Pest Pupil / director, Dave Tendlar ; animation, Morey Reden, George Germanetti ; story, Carl Meyer. The stupidstitious cat / Paramount presents a Noveltoon ; direction, Seymour Kneitel ; animation, Graham Place, John Walworth ; story, Carl Meyer, Jack Ward. Hep cat symphony / Paramount presents a Noveltoon ; direction, Seymour Kneitel ; animation, Dave Tendlar, Marty Taras ; story, Carl Meyer, Jack Mercer. Chese burglar / Paramount presents a Noveltoon ; direction, I. Sparber ; animation, Jim Tyer, Ben Solomon, William Henning ; story, Carl Meyer, Joe Stultz.
Title from the provider's web page.
Originally produced in the United States as motion picture between 1945 and 1957.
Music, Winston Sharples.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 20, 2015).
Keywords: Baby Huey (Fictious character) -- Drama; Buzzy (Fictious character) -- Drama; Herman (Fictious character) -- Drama; Animated films; Children's films; Short films; Internet videos; Streaming video